Cellular Biomechanics in Drug Screening and Evaluation: Mechanopharmacology. (February 2016) - Krishnan, Ramaswamy; Park, Jin-Ah; Seow, Chun Y.; Lee, Peter V-S.; Stewart, Alastair G.
Abstract : The study of mechanobiology is now widespread. The impact of cell and tissue mechanics on cellular responses is well appreciated. However, knowledge of the impact of cell and tissue mechanics on pharmacological responsiveness, and its application to drug screening and mechanistic investigations, have been very limited in scope. We emphasize the need for a heightened awareness of the important bidirectional influence of drugs and biomechanics in all living systems. We propose that the term 'mechanopharmacology' be applied to approaches that employ in vitro systems, biomechanically appropriate to the relevant (patho)physiology, to identify new drugs and drug targets. This article describes the models and techniques that are being developed to transform drug screening and evaluation, ranging from a 2D environment to the dynamic 3D environment of the target expressed in the disease of interest. Trends: An argument is outlined for a new interdiscipline: mechanopharmacology. Examples of cellular biomechanics influences on drug action are described. The relevance of matrix stiffness and of internal and external stresses to drug screening is discussed. Mtethods for the biomechanical perturbation and analysis of single cells and organoids are reviewed.